Pengaruh Beban Kerja dan Pembinaan Disiplin terhadap Kinerja Staf Bagian Kesatuan Pengamanan Rutan dan Subseksi Rutan Perempuan Kelas IIA Bandung - Sari, Novianty Ratna; Romi, Mochamad Vrans (J-MAS (Jurnal Manajemen dan Sains), 2024)
The decline in staff performance reviewed from the aspect of assessing the performance of the Bandung Class IIA Women's Prison staff still needs to be improved. The purpose of this study is to see the influence of workload and discipline coaching on performance partially and simultaneously. The study uses quantitative methods and questionnaires with interval scales as data collection. The research population is 32 staff of the Bandung Class IIA Women's Detention Center. Samples were taken using a saturated sampling technique. Data processing was analyzed using multiple regression analysis and hypothesis tests using partial (t-test) and simultaneous (F-test). This study proves that workload has a negative and significant effect on staff performance partially. Discipline coaching has a positive and significant effect on staff performance. Meanwhile, simultaneously workload and discipline coaching have a significant effect on staff performance.